PENGARUH STRUKTUR MODAL, STRUKTUR AKTIVA DAN MANAJEMEN MODAL KERJA TERHADAP KINERJA KEUANGAN - Wartiningsih, Ni Luh Putu; Candradewi, Made Reina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024, 2024)
Good financial performance is vital. It helps management make financial decisions and keep the business running long-term. Better financial performance makes it easier to get investments. The research uses a causality design to examine the relationship between capital structure, asset structure, and working capital management on the financial performance of transportation and logistics issuers in 2018-2022. The research uses a nonparticipant observation method. Data analysis techniques use multiple linear regression and apply SPSS version 25. The research findings are: First, capital structure has a significant negative effect on financial performance. Second, asset structure has a significant negative effect on financial performance. Third, working capital management has no insignificant effect on company finances. The theoretical review of research supports the pecking order theory. This theory suggests that debt is riskier than internal financing. Issuers and investors can apply these research findings to boost profits and guide investments. The research shows that company managers and investors should consider capital structure and asset structure. These two factors determine the issuer's profits.